A new source of oxygenated organic aerosol and oligomers - Liggio, J.; Li, S. -M. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2013)
A large oxygenated organic uptake to aerosols was observed when exposing ambient urban air to inorganic acidic and non-acidic sulfate seed aerosol. For non-acidic seed aerosol the uptake was attributed to the direct dissolution of primary vehicle exhaust gases into the aqueous aerosol fraction, and was correlated to the initial seed sulphate mass. The uptake of primary oxygenated organic gases to aerosols in this study represents a significant amount of organic aerosol (OA) that may be considered primary when compared to that reported for primary organic aerosol (POA), but is considerably more oxygenated (O : C similar to 0.3) than traditional POA. Consequently, a fraction of measured ambient oxygenated OA, which correlates with secondary sulphate, may in fact be of a primary, rather than secondary source. These results represent a new source of oxygenated OA on neutral aerosol and imply that the uptake of primary organic gases will occur in the ambient atmosphere, under dilute conditions, and in the presence of pre-existing SO4 aerosols which contain water. Conversely, under acidic seed aerosol conditions, oligomer formation was observed with the uptake of organics being enhanced by a factor of three or more compared to neutral aerosols, and in less than 2 min, representing an additional source of SOA to the atmosphere. This resulted in a trajectory in Van Krevelen space towards higher O : C (slope similar to -1.5), despite a lack of continual gas-phase oxidation in this closed system. The results demonstrate that high molecular weight species will form on acidic aerosols at the ambient level and mixture of organic gases, but are otherwise unaffected by subsequent aerosol neutralization, and that aerosol acidity will affect the organic O : C via aerosolphase reactions. These two processes, forming oxygenated POA under neutral conditions and SOA under acidic conditions can contribute to the total ambient OA mass and the evolution of ambient aerosol O : C ratios. This may be important for properly representing organic aerosol O: C ratios in air quality and climate models.